Dynamic characteristics of sandwich composite with debonding. (September 2019) - Idriss, M; El Mahi, A
The article presents the results of experimental and finite element analyses of the flexural vibration behavior sandwich composite with different debonding ratios. Sandwich composite consists of two thin skins composed of E-glass fiber and epoxy resin bonded to lightweight and weaker core material of PVC foams. Experimental tests using the impulse technique were performed on the sandwich constituents and sandwich composites with different debonding lengths. The modal dynamic characteristics of sandwich composite were measured and discussed for each debonding ratio. A finite element modeling was used to determine the natural frequencies, modal shapes, and stress and strain fields for each element of sandwich composites for each debonding ratio. The modal strain energy approach was used to determine the contribution of energies dissipated of the core and the skins in the total dissipated energy and the global damping of the different sandwich composites. The results obtained by this approach are compared with those obtained experimentally.